Evaluación del impacto de las políticas públicas del buen vivir en organizaciones agroproductivas solidarias de los cantones Paján y Santa Ana - Ganchozo Santana, Bryan Marlo (2019)
The objective of this research was to evaluate the impact of the public policies of Good Liviing (Buen Vivir) on solidarity-based organizations of agricultural production in the cantons Pajan and Santa Ana, considering that four methodological phases were structured that were important for the development of this work. The first phase dealt with the search of bibliographic references generating a theoretical database that allowed us to acquire knowledge to sustain the subject of study. The second phase was to diagnose the current situation of the OAPS that facilitated to calculate a sample of treatment and control allowing us to apply a survey and tabulate the data obtained through the program "SPSS" version 25 in such a way that information was collected. For the third phase the evaluation indicators were chosen based on the three dimensions of Good Living. Moreover, a comparative matrix was developed of the objectives, policies and guidelines of the PNBV to verify their degree of compliance in the organizations of agricultural production. Finally, in the fourth phase the effects of the impact that the policies have on the associativity were analyzed allowing us to conclude that not all the benefits of the policies are met in the OAPS since they do not have the support of the government and for that reason is that some associations disintegrate. At the end, it is recommended to member and non-member producers to carry out activities to benefit their productivity.